Picture perfect: Exploring the relationship between problematic TikTok use, physical appearance perfectionism, and upward physical appearance comparison on body appreciation - Katie O'Connor; Johannes Karl; Simon Dunne (Current Research in Behavioral Sciences)
Physical appearance perfectionism and upward physical appearance comparisons have a potential role in explaining how the use of popular social networking sites can negatively impact a person's body image. Although there is considerable research on the relationship between body image and problematic Instagram usage, there is little reported on TikTok use. Therefore, the aim of this study was to explore the mediating relationship of physical appearance perfectionism and upward physical appearance comparison between problematic TikTok use and body appreciation. The sample included 185 TikTok users. Serial mediation analysis revealed a significant indirect negative relationship between problematic TikTok use and body appreciation through physical appearance perfectionism, but not upward physical appearance comparison, or physical appearance perfectionism and upward physical appearance comparison in serial. Thus, with the rapid growth of TikTok, this study highlights the importance of identifying the individuals who may be more vulnerable to the effects of the app. We suggest possible practice implications such as the implementation of screening strategies to identify those high in physical appearance perfectionism, and the development of workshops aimed at promoting positive body image in the face of SNS use.